Injury Pattern among Bangladesh Army Recruits during Initial Training - Mohammad Mohsin, -; Md Shahidullah, -; Rahman, Md Mahbubur; Kabir, SM Humayan (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The recruit training period is the most formative part of a soldier’s life, full of both mental and physical challenges. They have to perform rigorous events under stressful conditions for a prolonged time. So they remain more vulnerable to injuries with their varied physical capabilities. Keeping in view the lack of injury data regarding recruit training in Bangladesh, scientific studies in this field bear immense importance. Objectives: To identify the common injuries encountered by recruits as well as the extent of the problem due to trainingrelated injuries and also to ascertain probable determinants for such injuries. Materials and Methods: This cross-sectional descriptive study was conducted from 1st January to 30th June 2012 in two training centres of Bangladesh Army. From all the 575 recruits undergoing training there, those reported sick or hospitalized and diagnosed as a case of training-related injury by a medical officer were taken in the sample. Interview schedule and checklist were used to collect data from 109 sample recruits. Results: Among total of 575 recruits 109 sustained injury at least once and 21 of them also sustained second injury. Lower extremity was found mostly (89%) affected and majority57.7% suffered from overuse injury. By diagnosis shin splint cases were the highest 36.7%. Among all the events highest 16.5% recruits were injured during participating in games and sports. The occurrence of injury was most (32.1%) during first four weeks of training. Among injured recruits 10.1% gave history of past injury which was found having statistically significant association with frequency of injury. Conclusion: Injury is a major impediment to recruit training. So, injury reduction through risk identification and appropriate intervention is imperative. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 123-126